2017
DOI: 10.7897/2230-8407.08691
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Method Development and Enhancement of Solubility of Clopidogrel Bisulfate

Abstract: Dissolution of drug is the rate determining step for oral absorption of the poorly water soluble drugs and solubility is the basic requirement for the absorption of the drug from GIT. The development of a soulful dissolution procedure for drug products with lower water solubility has been a provocation to both the pharmaceutical industry and the agencies that regulate them. This study demonstrates the systematic development o f a discriminatory dissolution method for clopidogrel bisulfate, a BCS class II drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The drug release of FDT-1 and FDT-2 was similar (f 2 >50) in both media, which may be due to the similar formulation parameters in both tablets. 8,20 Confirmation of discriminating dissolution test conditions Different dissolution profiles were obtained for FDTs of varying nature ( Figures 5 and 6). In the present study dissimilarity in drug release was observed with DOM-1 compared to DOM-2 in 0.5% SLS (f 2 =26) and similarity in drug release was observed with 0.1 N HCl (f 2 =58).…”
Section: Optimization Of Dissolution Test Conditionsmentioning
confidence: 78%
“…The drug release of FDT-1 and FDT-2 was similar (f 2 >50) in both media, which may be due to the similar formulation parameters in both tablets. 8,20 Confirmation of discriminating dissolution test conditions Different dissolution profiles were obtained for FDTs of varying nature ( Figures 5 and 6). In the present study dissimilarity in drug release was observed with DOM-1 compared to DOM-2 in 0.5% SLS (f 2 =26) and similarity in drug release was observed with 0.1 N HCl (f 2 =58).…”
Section: Optimization Of Dissolution Test Conditionsmentioning
confidence: 78%
“…Then a calibration curve was plotted concentration in μg/ml on X-axis and absorbance on Y-axis. 9 Fourier Transport Infrared Spectroscopy:…”
Section: Methodsmentioning
confidence: 99%
“…Differential scanning calorimetry and XRD demonstrate that lyophilized clopidogrel powder and tablet are amorphous. [75] Zhao et al precipitated genipin of mean PS of 1.8l μm with entire chemical structure and reduced crystallinity were reported as observed by scanning electron microscope (SEM) and thermogravimetric analysis, which resulted in a faster dissolution and better bioavailability than crystals. The dissolution rate and solubility were 2.08 and 1.64 times that of raw crystal, respectively.…”
Section: Antisolvent Precipitation Of Apismentioning
confidence: 99%
“…Differential scanning calorimetry and XRD demonstrate that lyophilized clopidogrel powder and tablet are amorphous. [ 75 ]…”
Section: Application Of Mixing For the Precipitation Of Apismentioning
confidence: 99%